PENERAPAN MODEL PEMBELAJARAN TUNTAS SELAMA KEGIATAN BELAJAR MENGAJAR PADA MATERI POKOK PENJUMLAHAN DAN PENGURANGAN DI KELAS I SD NEGERI PENAMPEN - DANIEL PAOLOROSI (JURNAL ILMIAH MAKSITEK, 2019)
Studi was to determine student’s grade I SDN 1 Penampen by applying learning model completed on the principal artery of addition and subtraction. These subject were taken First Grade Primary Years Learning 2010/2011 of SD Negeri Penampen, The number of student to 35 people. Student learing outcomes by implementing Complete Learning Model in Cycle I and Cycle II shows the individual completely sebanayk 30 student, and 35 students. Mastery classroom in Cycle I and cycle II were 85.7% and 100%. The calculation of the average score for the class of indicators like the subjects of 96.5 and 89.4 curiosity toward learning; thus curiosity to subject classified as very high. Similarly, indicators of desire to help a friend in learning kalsikalnya 86.3; thus the desire to help a friend in learning is high. Neverthekess, the studens seem to be more interested in the subject and his curiosity was slightly higher than with helping her to work in groups.